Studi Kelayakan Teknis Pembangunan Pelabuhan Angkutan Laut Pelayaran Rakyat 1000 DWT Di Sebalang - Jokowinarno, Dwi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
Based on Undang-Undang Republik Indonesia Nomor 17 Tahun 2008 of Navigation, waterwaytransportation consists of: (a) sea-based transportation; (b) River and lake transportation; (c)ferry. Meanwhile, sea-based transportation consist of: (a) domestic; (b) abroad; (c) special; and(d) traditional. Development of traditional sea-based transportation is aimed to keep the importantrole of traditional sea-based transportation as part of national sea-based transportation. Theimportance are: (1) to improve servicing to remote area; (2) impact on national economy; and (3)to improve competency and entrepreneurship. Development of Sebalang Traditional Sea-BasedPort is technicaly feasibel. Special issues that may occur are social, economic, and financing.